Effect of radiation dose on the properties of natural rubber nanocomposite - Khalid, M.; Ismail, Ahmad Faris; Ratnam, Chantara Thevy; Yusof, Faridah; Rashmi, W.; Al-Khatib, Ma'an Fahmi Rashid (Elsevier, 2010)
Effect of radiation dose and carbon nanotubes (CNT) on the mechanical properties of standard Malaysian rubber(SMR) was investigated in this study.SMR nanocomposites containing 1–7 phr CNT were prepared using the solvent casting method and the nanocomposites were radiated at doses of 50–200 kGy. The change in mechanical properties, especially, tensile strength (Ts), elongation at break (Eb), hardness and tensile modulus at 100% elongation (M100) were studied as a function of radiation dose. The structure and morphology of reinforced natural rubber was investigated by FESEM, TEM and AFM in order to gain further evidence on the radiation-induced crosslinking. It was found that the Ts, M100 and the hardness of the SMR/CNT nanocomposites significantly increased with radiation dose; the elongation at break exhibited an increase up to 100 kGy, and a downward trend thereafter. Results on gel fraction further confirmed the crosslinking of SMR/CNT nanocomposites upon radiation.